2008
DOI: 10.1172/jci33467
|View full text |Cite
|
Sign up to set email alerts
|

Excess adenosine in murine penile erectile tissues contributes to priapism via A2B adenosine receptor signaling

Abstract: Priapism, abnormally prolonged penile erection in the absence of sexual excitation, is associated with ischemia-mediated erectile tissue damage and subsequent erectile dysfunction. It is common among males with sickle cell disease (SCD), and SCD transgenic mice are an accepted model of the disorder. Current strategies to manage priapism suffer from a poor fundamental understanding of the molecular mechanisms underlying the disorder. Here we report that mice lacking adenosine deaminase (ADA), an enzyme necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
226
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(243 citation statements)
references
References 50 publications
13
226
1
3
Order By: Relevance
“…It has been demonstrated that endogenous adenosine through A2B adenosine receptor play important role in the physiological process of penile erection (Wen et al 2011a, b) and excess adenosine, also via ADORA2B, leads to priapism in ADA deficient mice and sickle cell disease Tg mice (Mi et al 2008;Wen et al 2010a, b). In additional, Faria et al (2006) reported that vasculogenic erectile dysfunction is resistant to adenosine relaxation due to endothelial dysfunction caused by decreased activation of ADORA2B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that endogenous adenosine through A2B adenosine receptor play important role in the physiological process of penile erection (Wen et al 2011a, b) and excess adenosine, also via ADORA2B, leads to priapism in ADA deficient mice and sickle cell disease Tg mice (Mi et al 2008;Wen et al 2010a, b). In additional, Faria et al (2006) reported that vasculogenic erectile dysfunction is resistant to adenosine relaxation due to endothelial dysfunction caused by decreased activation of ADORA2B.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported by our early work that endogenous adenosine through ADORA2B plays important role in the physiological process of penile erection in smooth muscle cells by two mechanisms: direct induction of cAMP production and indirect induction of cGMP production following the activation of eNOS in endothelial cells via the PI3K/AKT signaling cascade (Wen et al 2011a, b). Additionally, excess adenosine lead to priapism in adenosine deaminase (ADA) deficient mice and sickle cell disease transgenic (Tg) mice, also via ADORA2B (Mi et al 2008;Wen et al 2010a, b). Moreover, Faria et al (2006) reported that adenosine regulates smooth muscle tone of human corpus cavernosum through the activation of A2A and A2B adenosine receptors, which are located on smooth muscle fibers and on endothelial cells, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility has been raised that elevated adenosine signalling contributes to priapism, a condition of persistent penile erection lasting at least 4 h in the absence of sexual excitation [86,305]. Excess adenosine in penile erectile tissue in mice lacking adenosine deaminase contributes to priapism via A 2B receptor signalling [272]. A recent review highlights adenosine signalling pathways operating in penile tissue as significant therapeutic targets for the treatment of erectile disorders [430].…”
Section: Penis and Penile Erectionmentioning
confidence: 99%
“…80 Adenosine actions on ED have been explored in obese and type 2 diabetic db/db mouse 81 as well as in A2B receptor-knockout mice. 82 Mouse models of NO pathway disruption have been critical in defining the role of vasodilators as targets for the treatment of ED. 83 --86 The cGMP kinase I-deficient mouse has also been used to better understand the role of smooth muscle cells in the pathogenesis of ED.…”
Section: Animal Modelsmentioning
confidence: 99%